2001
DOI: 10.1093/ptj/81.5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation in Physical Therapy Goal Setting

Abstract: Background and Purpose. An important part of treatment planning in physical therapy is effective goal setting. The Guide to Physical Therapist Practice recommends that therapists should identify the patient's goals and objectives during the initial examination in order to maximize outcomes. The purpose of this study was to examine whether therapists seek to involve patients in goal setting and, if so, what methods they use. Therapists' attitudes toward participation and patient satisfaction with the examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 7 publications
2
60
0
Order By: Relevance
“…This mismatch between nurses' discursive accounts of their practice and their practical demonstration of this activity is not an uncommon finding. Baker et al . found clinicians rated themselves highly in seeking to involve patients in physical therapy goal setting; however, observations of practice indicated that few clinicians actually engaged patients in collaborative goal setting at any time.…”
Section: Discussionmentioning
confidence: 99%
“…This mismatch between nurses' discursive accounts of their practice and their practical demonstration of this activity is not an uncommon finding. Baker et al . found clinicians rated themselves highly in seeking to involve patients in physical therapy goal setting; however, observations of practice indicated that few clinicians actually engaged patients in collaborative goal setting at any time.…”
Section: Discussionmentioning
confidence: 99%
“…Homebased child-care skills [23] and adaptive equipment use [2] for children with cerebral palsy can reduce the degree of the caring burden and, subsequently, reduce some of the parenting stress. Clinical professionals should also facilitate parents' participation in goal-setting for their child's therapy [24]. This could help to increase parents' satisfaction in their child's improvement and also to decrease parents' distress.…”
Section: Discussionmentioning
confidence: 99%
“…25 Physical therapists' experience with this population and increasing demands on their time and resources may lead them to target particular clients with certain demographic variables for more frequent or higher volumes of SM goals. 26 Examining the impact of factors known to influence clients' SM behaviour, such as sex, age, or number of chronic conditions, on SM goal setting by community-based physical therapists may provide insight into factors driving goalsetting practices, contributing to the identification of strategies to improve SM in home and community care.…”
Section: Goal Descriptormentioning
confidence: 99%